Maps, Synagogues, the City of Vilne, and Zalmen Szyk - Levin, Vladimir (Colloquia, 2021)
The absolute majority of maps of East European cities marked only one or two major synagogues, while tens or hundreds of smaller synagogues and Jewish prayer houses were omitted. Using Vilnius as a case study, the article argues that this omission was not only a consequence of viewing the Jews as a ‘not indigenous’ part of the population, but also reflected the reality. The absolute majority of synagogues and prayer houses had no role in the cityscape of Vilnius and other cities of Eastern Europe, and therefore were not noticeable to non-Jewish people. Either synagogues and prayer houses were situated in courtyards, or they had no external features designating them as Jewish sacred places. Only the Great Synagogues and the Choral Synagogues of ‘modernised’ Jews attempted to be visible and prominent in the cityscape. The discussion of the issue of visibility of Jewish sacral buildings is based on the Yiddish guidebook to the city of Vilnius published by Zalmen Szyk in 1939. This book is a unique work, which combines the description of Vilnius ‘in general’ with special attention paid to the Jewish public institutions existing in the city, the majority of them synagogues and prayer houses.
Keywords: Vilnius; synagogues; Jewish history in Eastern Europe; maps; guidebooks; Zalmen Szyk